Estudo da estabilidade de compostos bioativos do fruto e da polpa de acerola (Malpighia emarginata D.C.) submetidos a processos de congelamento criogênico e mecânico - Aquino, Ana Carolina Moura de Sena (2009)
Acerola (Malpighia emarginata D.C.) is a fruit much valued for its color and also for its high vitamin C content, as being among the main Brazilian products targeted for export. The color change, going from red to yellow, is one of the main changes observed during storage of frozen acerola fruits. Cryogenic shown an advantage over the conventional freezing because the water content of the cells to freeze quickly ensures the formation of very small crystals that produce less damage to cell structure allowing better maintenance of product quality. The Chapter 1 did the stability study of the whole acerola fruits frozen by conventional methods (mechanical cold at -22.1°C) and cryogenic (by immersion in nitrogen vapor at -180,9°C, N2(v) and in liquid nitrogen at -196,2°C, N2(l)) during storage at -22.1°C for 60 days. The mean times of freezing of the acerola fruits by cold mechanical, N2(v) and N2(l) were, respectively, 3.5 hours, 14 minutes and 4.5 minutes. The cryogenic methods resulted in increased retention of carotenoids in relation to the mechanical cold, after 60 days, as the acerola fruits reductions of 7.64%, 5.20% and 4.75% respectively for samples frozen conventionally, for N2(v) and N2(l), respectively. Until the 60th day, the conventional method was that provided the greatest reduction (16.64%) of total anthocyanins of fruits. Decreases were observed for the parameters a*, b* and C*, and increases to L* and h, for all methods of freezing during storage, these being higher for conventionally frozen fruit. Frozen samples by N2(v) and N2(l) had the lowest ∆E * values in relation to the standard, in other words, less change in color after 60 days of storage at -22.1 ° C. In Chapter 2 was evaluated the effect of mechanical freezing (conventional at -22.1°C) and cryogenic methods (immersion in N2(v) at -178.6°C and immersion in N2(l) at -195.1°C) in the stability of the pulp acerola during storage for 120 days at -22.1°C. The mean times of freezing of the pulp acerola by mechanical cold at -22.1°C, for N2(v) at -178.6°C and for N2(l) at -195.1°C were, respectively, 3.8 hours, 20 minutes and 3 minutes. The levels of xviii ascorbic acid were stable for all methods of freezing, but after 90 days of storage, the pulp frozen conventionally, for N2(v) and N2(l) showed reductions in total carotenoids of 16.45%, 11.48% and 6.60% respectively, compared to the standard and these were sustained until the 120th day. The smallest difference in color (∆E*) was observed for the sample frozen by vapor of N2, and this had the highest retention of anthocyanins (91.50%) by the end of the experiment, while the sample immersed in N2(l) had the lowest retention of these pigments (71.54%). For microbiological results, all samples were under the maximum allowed by law. For the acceptance test, the different methods of freezing did not affect the acceptability of juices made from the pulp. On the results, the cryogenic freezing in nitrogen vapor is presented as a good alternative to higher retention of the pigments that give color and bioactivity of the acerola pulp. The application of cryogenic freezing, either by immersion in vapor as in liquid N2 before the cold mechanical proved advantageous for the storage of the acerola fruits, however for the pulp, the freezing by nitrogen vapor was the best method, because it propitiated greater maintenance of its pigments and also bioactive components.